Oral Biopsy in General Dental Practice: A Review (International Journal of Food and Nutritional Sciences, 2022)
The identification of disorders of the oral mucosa and subsequent treatment planning are both deemed to require an oral biopsy. All medical disciplines routinely employ biopsies; yet, dental professionals do not frequently do them; this may be due to dental surgeons' ignorance of the procedure. The oral pathologist's aptitude for analysing a lesion is largely relies on a successful biopsy that the dental surgeon does. This review's goal is to discuss indications, oral biopsy contraindications and major potential hazards that may occur during the biopsy process, In an effort to better understand how dental surgeons identify pre-malignant and malignant lesions, Here, it is also explained how to aid in reducing the prevalence of oral cancer.